Projections of the Mouse Primary Visual Cortex - Resulaj, Arbora (Frontiers in Neural Circuits, 2021)
Lesion or damage to the primary visual cortex (V1) results in a profound loss of visual perception in humans. Similarly, in mice, optogenetic silencing of V1 profoundly impairs discrimination of orientated gratings. V1 is thought to have such a critical role in perception in part due to its position in the visual processing hierarchy. It is the first brain area in the neocortex to receive visual input, and it distributes this information to more than eighteen brain areas. Here I review recent advances in our understanding of the organization and function of the V1 projections in the mouse. This progress is in part due to new anatomical and viral techniques that allow for efficient labelling of projection neurons. In the final part of the review, I conclude by highlighting challenges and opportunities for future research.